2016
DOI: 10.1093/icvts/ivw197
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal paraganglioma fed by the left circumflex artery

Abstract: A 60-year-old male patient who previously underwent carotid and jugular paraganglioma resections was referred because of a mediastinal recurrence at the root of the great vessels. Coronary angiography confirmed the circumflex artery of the left coronary artery as the feeding artery of the tumour. The patient underwent surgery due to the tumour's location and malignant potential. Upon mass resection, histopathological examination characterized the tumour as a secondary paraganglioma. Neuroendocrine tumours aris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…An additional 2.5% mortality was reported for the immediate postoperative course. A review of individual case reports from 2014-2016, two years since Wang et al's review, shows no intraoperative mortality reported from 11 cases (12,18,19,(22)(23)(24)(25)(26)(27). Among these cases, one instance of intraoperative cardiac arrest occurred due to severe hemorrhage and one unexpected intraoperative circulatory collapse, however both ended with successful outcomes (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…An additional 2.5% mortality was reported for the immediate postoperative course. A review of individual case reports from 2014-2016, two years since Wang et al's review, shows no intraoperative mortality reported from 11 cases (12,18,19,(22)(23)(24)(25)(26)(27). Among these cases, one instance of intraoperative cardiac arrest occurred due to severe hemorrhage and one unexpected intraoperative circulatory collapse, however both ended with successful outcomes (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of paragangliomas varies with tumor location, degree of tumor burden, and secretory functionality. Functional paragangliomas secrete excessive catecholamines resulting in a clinical presentation of paroxysmal hypertension, headache, sweating, and palpitations [ 3 , 7 ]. Non-functional paragangliomas typically present with symptoms such as dysphagia, angina, or dyspnea as a result of a compressive mass effect on adjacent structures [ 3 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional paragangliomas secrete excessive catecholamines resulting in a clinical presentation of paroxysmal hypertension, headache, sweating, and palpitations [ 3 , 7 ]. Non-functional paragangliomas typically present with symptoms such as dysphagia, angina, or dyspnea as a result of a compressive mass effect on adjacent structures [ 3 , 7 ]. Mediastinal paragangliomas are estimated to make up 0.3% of all mediastinal tumors and less than 2% of all paragangliomas [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…AorticopulmonaryPGLofsuperiorandmiddlemediastinumoccursinpatientswithmeanageof49yearsand catecholaminesecretionisdetectedinonly3%ofcas-es.TheparavertebralPGLsofposteriormediastinum ariseinyoungerpatientswithameanageof29years andalmosthalfofthesetumorsarehormonallyactive [10,11].MediastinalPGLstendtoinvadetoneighboringorgans,thusbecominghardertoremove [12,13]. Posterolateral thoracotomy or median sternotomyrepresenttherecommendedsurgicalapproaches.Inacaseofgreatvesselingrowthorhighriskof bleeding, cardiopulmonary bypass may be required [9,14]. If there is a suspicion of functioning PGL, abiopsyorresectioncanbeperformedonlyafteralpha-adrenergicblockademedication,becausesurgery cancauseseverehypertensionfromcatechomalmine crisis.Duetotheunpredictablemalignantpotential of PGLs, radical surgical excision is highly recommended with subsequent careful follow-up to rule out delayed metastatic spread.…”
Section: Discussionmentioning
confidence: 99%